2020
DOI: 10.3991/ijet.v15i03.10628
|View full text |Cite
|
Sign up to set email alerts
|

M-WebQuest Development: Reading Comprehension of Senior High School Students in Indonesia

Abstract: M-WebQuest is a teaching model adapted from WebQuest created firstly by Bernie Dodge, where its development is used ADDIE model. This research aims to develop M-WebQuest to improve reading comprehension attainment of senior high school students Grade XI in Pekanbaru, Riau – Indonesia. In gaining the feasibility of the developed M-WebQuest, 3 experts, 10 English teachers and 30 students were involved. Based on the given questionnaire analysis, the experts agree on the feasibility of created M-WebQuest in terms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 8 publications
0
12
0
1
Order By: Relevance
“…Several studies have been conducted using the WebQuest approach (Kazakova & Kloyster, 2018;Ebadi & Rahimi, 2018;Sakadineca & Jansone, 2018;Chen, 2019;Adanan, Adanan & Herawan, 2020). These studies have shown that the WebQuest process supports the learners' level of learning engagement and the level of enjoyment of their studies.…”
Section: What Is Webquest?mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have been conducted using the WebQuest approach (Kazakova & Kloyster, 2018;Ebadi & Rahimi, 2018;Sakadineca & Jansone, 2018;Chen, 2019;Adanan, Adanan & Herawan, 2020). These studies have shown that the WebQuest process supports the learners' level of learning engagement and the level of enjoyment of their studies.…”
Section: What Is Webquest?mentioning
confidence: 99%
“…Researchers claim that the WebQuest technology, as an interactive method, can be successfully implemented in the field of teaching foreign languages. They believe that after the implementation of WebQuest and other learning methods such as collaborative projects, problem-based classrooms or flipped classrooms in the field of language acquisition, the learners' language competency performance will be significantly improved (Awada & Dihab, 2018;Berezova et al, 2018;Adanan et al, 2020;Synekop, 2020). Awada and Dihab (2018) investigated student's academic writing performance after integrating Student Team Achievement Division (STAD) and WebQuest into their learning process.…”
Section: What Is Webquest?mentioning
confidence: 99%
“…Today, educational platforms, digital tools and web applications are transforming the organization of the school activities in the high schools (ADANAN et al, 2020;ZHANG, 2020). In fact, the students actively participated in the courses of Biology (GARIOU-PAPALEXIOU et al, 2017), English Language (BARDAKCI et al, 2018;ZHANG, 2020), Science (SMITH et al, 2019, Physics (ADAM; SUPRAPTO, 2019) and Life Basics (PABRUA-BATOON et al, 2018) through the use of technology.…”
Section: Use Of Technology In the High Schoolsmentioning
confidence: 99%
“…Finally, ICTs are changing the behavior of teachers and students in the high schools (ADANAN et al, 2020;WU et al, 2020). In fact, educational institutions promote the organization and implementation of student-centered activities through technology (HE et al, 2020;OYINLOYE;IMENDA, 2019).…”
Section: Use Of Technology In the High Schoolsmentioning
confidence: 99%
See 1 more Smart Citation